Profiles of districts : November 1993 - Centre for monitoring Indian economy (Bombay, 1993)
This document contains statistical profiles on 466 districts of India. The precise names correspond to those presented in the 1991 Population Census. The presentation is organised by State. States are sequenced alphabetically, and the districts within a State are also organised alphabetically. A full alphabetical index of all the districts is presented in the pages following this Explanatory Note. Fifty-four new districts were added between 1981 and 1991. In many cases, the data available are not segregated according to the new sub-division of the old existing districts.
Keywords: Districts-India-Statistics-1993